(untitled) (Research, Society and Development, 2021)
This work has the purpose of mapping the scientific production of researchers recipient of CNPq productivity grants in research (PQ) and productivity grants in technological development and innovative extension (DT), in the Production Engineering field, in the four-year period from 2013 to 2016. The information was extracted from the Lattes Platform, on which we obtained quantitative data about the individual scientific production of 190 researchers, through the software scripLattes v8.10. The data analysis was conducted through descriptive statistics, the Kolgomorov-Smirnov data normality test, the Kruskal-Wallis test, and the Mann-Whitney test. The results show that 76% of the researchers compose the PQ grant category. Within the four-year period, among PQ researchers, 1B and 1A researchers had the best average of total published articles, with 19.42 and 15.75 articles per researcher, respectively. Among DT researchers, 1D and level 2 researchers had, in average, 21.5 and 12.57 published articles, respectively. PQ researchers maintain their production of scientific articles homogeneous at all Qualis levels. On the other hand, DT researchers present greater heterogeneity in their publications. It is possible to conclude that level 1 researchers do not focus on journals that present low Qualis ratings for the publication of their research. In contrast, level 2 researchers are less experienced and expect to publish in higher-level journals, but when their works are rejected, they start “betting” on journals of lesser quality.